2020
DOI: 10.14746/hl.2020.13.10
|View full text |Cite
|
Sign up to set email alerts
|

Escape room as an adult education tool

Abstract: Games gain popularity as teaching tools. Escape rooms, however, are a novelty, with most authors focusing on their description rather than the analysis of effects of their utilisation. The objective of this paper is to analyse experiences of players partaking in an educational escape game, and to observe escape rooms from the viewpoint of a scholar interested in the efficiency of the tool. The research material consists of questionnaires filled in by research subjects and transcripts of structured interviews. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The use of Escape Rooms (ERs) as a game-based learning activity can be considered a relatively new but not anymore uncommon educational practice internationally. Several educational ER experiences and studies have been reported in higher and adult education (Fotaris and Mastoras, 2019;Mijal et al, 2020;Veldkamp et al, 2020), while only a limited body of work explores the same topic in middle-school, primary school or kindergarten (Fotaris and Mastoras, 2019;Hod-Shemer and Dabush, 2020;Babazadeh and Frigerio, 2021;Babazadeh, Botturi & Reggiani, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The use of Escape Rooms (ERs) as a game-based learning activity can be considered a relatively new but not anymore uncommon educational practice internationally. Several educational ER experiences and studies have been reported in higher and adult education (Fotaris and Mastoras, 2019;Mijal et al, 2020;Veldkamp et al, 2020), while only a limited body of work explores the same topic in middle-school, primary school or kindergarten (Fotaris and Mastoras, 2019;Hod-Shemer and Dabush, 2020;Babazadeh and Frigerio, 2021;Babazadeh, Botturi & Reggiani, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Educational Escape Rooms (EERs) as a game-based learning activity have become popular in the past few years, especially in higher education. While many EERs have been studied in higher or adult education (Fotaris and Mastoras, 2019;Mijal et al, 2020;Veldkamp et al, 2020), only a limited body of work explores EERs in middleschool, primary school or kindergarten (Fotaris and Mastoras, 2019;Hod-Shemer and Dabush, 2020;Babazadeh and Frigerio, 2021).…”
Section: Introductionmentioning
confidence: 99%